2020
DOI: 10.3390/jcm9051394
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Soluble CD93 in Type 2 Diabetes as a Biomarker for Diabetic Nephropathy: Integrated Results from Human and Rodent Studies

Abstract: Cluster of differentiation 93 (CD93) is a glycoprotein expressed in activated endothelial cells. The extracellular portion of CD93 can be secreted as a soluble form (sCD93) under inflammatory conditions. As diabetic nephropathy (DN) is a well-known inflammatory disease, we hypothesized that sCD93 would be a new biomarker for DN. We prospectively enrolled 97 patients with type 2 diabetes and evaluated the association between serum sCD93 and DN prevalence. The association between CD93 and development of DN was i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 40 publications
2
21
1
Order By: Relevance
“…The soluble form (sCD93) results from metalloproteinase-dependent shedding of CD93 extracellular domain [ 4 ]. The sources of circulating sCD93 include monocytes, neutrophils, and endothelial cells stimulated by inflammatory mediators (tumor necrosis factor α–TNFα and lipopolysaccharide) [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The soluble form (sCD93) results from metalloproteinase-dependent shedding of CD93 extracellular domain [ 4 ]. The sources of circulating sCD93 include monocytes, neutrophils, and endothelial cells stimulated by inflammatory mediators (tumor necrosis factor α–TNFα and lipopolysaccharide) [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are single reports linking sCD93 with renal diseases, i.e., diabetic nephropathy in type 2 diabetes [ 6 ], and renal involvement in antineutrophil cytoplasmic antibody associated vasculitis [ 16 ]. In 2016, Ikewaki et al [ 20 ] reported a strong correlation between sCD93 and serum creatinine and cystatin C in 14 patients with chronic kidney failure.…”
Section: Introductionmentioning
confidence: 99%
“…Neutrophil degranulation [52], innate immune system [53], platelet degranulation [54], extracellular matrix organization [55], diseases of glycosylation [56], platelet activation, signaling and aggregation [57], hemostasis [58], secretion [59], secretory vesicle [60], transmembrane transporter activity [61], cell adhesion [62], localization of cell [63], extracellular matrix [55], intrinsic component of plasma membrane [64], structural molecule activity [65], signaling receptor binding [66], have been highly noted in T2DM. Reports indicate that HIF1A [67], HLA-DRB1 [68], CHI3L1 [69], ADORA2A [70], ADRB2 [71], CLU (clusterin) [72], AGT (angiotensinogen) [73], VCAM1 [74], PPARA (peroxisome proliferator activated receptor alpha) [75], APOL1 [76], ZFP36 [77], PPM1B [78], SOCS1 [79], SNCA (synuclein alpha) [80], CTSS (cathepsin S) [81], IL6R [82], CFB (complement factor B) [83], DEFB1 [84], VNN1 [85], RAB27A [86], DPP4 [87], RARRES2 [88], CASP1 [89], LCN2 [90], REG3A [91], CD74 [92], PCSK2 [93], CHGB (chromogranin B) [94], TTR (transthyretin) [95], LRG1 [96], ALB (albumin) [97], DPP7 [98], APOH (apolipoprotein H) [99], CTSD (cathepsin D) [100], GCG (glucagon) [101], KCNQ1 [102], NR4A1 [103], PLIN5 [104], ALDH2 [105], ANG (angiogenin) [106], CLDN7 [107], PRLR (prolactin receptor) [108], SOD2 [109], MLXIPL (MLX interacting protein like) [110], CTSD (cathepsin D) [111], PECAM1 [112], ADA (adenosine deaminase) [113], MFGE8 [114], COL1A1 [115], COL3A1 [116], NID2 [117], ARG1 [118], CD93 [119], IGF2 […”
Section: Discussionmentioning
confidence: 99%
“…A total of 925 DEGs (447 up regulated genes and 478 down regulated genes) were screened between T2DM and control samples. Emmens et al [39] found that PENK [110], CTSD (cathepsin D) [111], PECAM1 [112], ADA (adenosine deaminase) [113], MFGE8 [114], COL1A1 [115], COL3A1 [116], NID2 [117], ARG1 [118], CD93 [119], IGF2 [120], IL18 [121], LAMA1 [122], HPSE (heparanase) [123], BMP4 [124] [132], MMP3 [133], MMP9 [134], MMP11 [135], IL16 [136], TNFRSF11B [137], TIMP3 [138] and CAPN3 [139] were found in T2DM. HLA-A [140], HLA-B [141], HLA-C [142], HLA-DPB1 [143], HLA-E [144], ERBB3 [145], MFAP4 [146] and JAK3 [147] have been reported significantly expressed in type 1 diabetes mellitus, but these genes might be involved in T2DM progression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation